True believer - Wolff, Virginia Euwer (2002)
Living in the inner city amidst guns and poverty, fifteen-year-old LaVaughn learns from old and new friends, and inspiring mentors, that life is what you make it--an occasion to rise to. In this second novel of Wolff's "Make Lemonade" trilogy, 15-year old Verna LaVaughn is visited by Jody, a boy she knew as a child who comes back to the housing project where she lives. Jody behaves as if he's in love with her, but Jody is wrestling with questions of his own identity.
Michael L. Printz Honor for Excellence in Young Adult Literature, 2002.
Keywords: Single-parent families -- Young audlt fiction; Poor -- Young audlt fiction; Friendship -- Young audlt fiction; Conduct of life -- Young audlt fiction; Poor families -- Young audlt fiction; Poverty -- Young audlt fiction; Sex -- Young audlt fiction; Teenage girls -- Young audlt fiction; Friendship -- Young audlt fiction; Conduct of life -- Young audlt fiction